Etnoastronomi Masyarakat Nelayan Cilellang Kabupaten Barru Perspektif Ilmu Falak - Sani, NurHaslina; Alimuddin,; Irfan, (HISABUNA: Jurnal Ilmu Falak, 2025)
This type of research is field research that uses a descriptive qualitative method. This study was conducted by collecting data and then analyzing the research results based on the facts obtained in the field. Data collection uses primary and secondary data sources. Primary data sources are literature sources such as books, journals, and dissertations that serve as supporting references in the research. Secondary data sources come from research obtained in the field through interviews and documentation to obtain clear information regarding the Ethnoastronomy of the Cilellang Fishing Community in Barru Regency from the Perspective of Astronomy. The results of the research indicate that the Cilellang Village Fishing Community still applies some elements of traditional meteorology, which we call ethnoastronomy. They use the sun, moon, and star clusters as guidelines. The movement of the sun and moon is used to determine the condition of the day and weather, whether good or bad, in their daily activities as fishermen, which is recorded in the lontara' manuscripts. Star constellations or "anak uleng" are used as natural signs to determine all directions. In the perspective of astronomy, star constellations can be used to determine the direction of the Qibla, such as the Ursa Major constellation, known as "anak uleng kappalae," which indicates the north direction, and the Orion constellation, known as "anak uleng tellue-tellue," which indicates the west direction. It is recommended that more in-depth research be conducted related to the accuracy of cardinal directions using star constellations. .Keywords: Ethnoastronomy, Fisherman Communities, Astronomy